Ventral tegmental area GABA neurons and opiate motivation - Ting-A-Kee, Ryan (2013)
RATIONAL: Past research has demonstrated that when an animal changes from a previously drug-naive to an opiate-dependent and withdrawn state, morphine’s motivational effects are switched from a tegmental pedunculopontine nucleus (TPP)-dependent to a dopamine-dependent pathway. Interestingly, a corresponding change is observed in ventral tegmental area (VTA) GABA(A) receptors, which change from mediating hyperpolarization of VTA GABA neurons to mediating depolarization. OBJECTIVES: The present study investigated whether pharmacological manipulation of VTA GABA(A) receptor activity could directly influence the mechanisms underlying opiate motivation. RESULTS: Using an unbiased place conditioning procedure, we demonstrated that in Wistar rats, intra-VTA administration of furosemide, a Cl(−) cotransporter inhibitor, was able to promote a switch in the mechanisms underlying morphine’s motivational properties, one which is normally observed only after chronic opiate exposure. This behavioral switch was prevented by intra-VTA administration of acetazolamide, an inhibitor of the bicarbonate ion-producing carbonic anhydrase enzyme. Electrophysiological recordings of mouse VTA showed that furosemide reduced the sensitivity of VTA GABA neurons to inhibition by the GABA(A) receptor agonist muscimol, instead increasing the firing rate of a significant subset of these GABA neurons. CONCLUSION: Our results suggest that the carbonic anhydrase enzyme may constitute part of a common VTA GABA neuron-based biological pathway responsible for controlling the mechanisms underlying opiate motivation, supporting the hypothesis that VTA GABA(A) receptor hyperpolarization or depolarization is responsible for selecting TPP- or dopamine-dependent motivational outputs, respectively.